ROLE OF SMALL VESSEL THROMBO-EMBOLECTOMY IN LOWER LIMB SALVAGE AND ITS CLINICO PATHOLOGICAL SPECTRUM IN ACUTE LIMB ISCHEMIA - NASIR, M; SADIQ, I; MUSHTAQ, A (Biological and Clinical Sciences Research Journal, 2024)
Acute limb ischemia (ALI) is a vascular emergency where prompt intervention is crucial to salvage the limb. The standard treatment window is within 6 hours; beyond this period, the limb is presumed to suffer irreversible ischemic damage. However, surgical interventions like retrograde thrombo-embolectomy offer hope for limb salvage even in delayed presentations. This study investigates the efficacy of retrograde thrombo-embolectomy in small distal vessel occlusions due to thrombus or embolus in patients presenting after the 12-hour mark. Objective: To report the patients who presented to us beyond the 6-hours mark, beyond which the limb is presumed to have developed irreversible ischemic changes. The efficacy of retrograde thrombo-embolectomy in distal small vessel occlusion secondary to thrombus or embolus in delayed presentation of ALI was also evaluated. Methods: Thirty-five cases presented with acute limb ischemia for more than 12 hours. All Rutherford Grade IIa, IIb were included in the study. A prospective cross-sectional study was conducted and intra-operative findings, outcomes, post-operative complications were noted. All selected patients were operated by open surgery approach consisting of CFA thrombectomy and retrograde PTA/ATA Thrombo-embolectomy at ankle depending on thrombus site. Results: The study demonstrated a 97.1% success rate in limb salvage and functionality over 6 months follow-up. One patient had a major complication of re-thrombosis for which a repeat procedure was done. Four patients developed minor complications such as wound infection, ray amputation, needing wound debridement. Conclusion: Surgical intervention is possible for acute ischemic limb with delayed presentation (>12 hour). An open surgical approach is a safe and reliable option in such patients. However, further research is needed with a wider study population to actually see benefits of surgical intervention in delayed ALI presentation.